Long-Run IPO Performances and Its Influencing Factors: The Case of Indonesian Stock Exchange - Mahardhini Fuadillah; Agus Harjito (Jurnal Siasat Bisnis, 2009)
The objective of this study is to find whether Indonesian stock exchange will also show long-run underperformance of IPO or not, and what are factors influence the long-run underper-formance that happens in a company after IPO. Factors influencing IPO performances are repre-sented by four variables are age, time lag, issue size, and company size. Long run IPO perform-ance is represented by Buy-and-Hold Adjusted Return (BHAR). This study employs data from companies listed in Indonesian Stock Exchange (IDX), which are going public from 2000 to 2005. The results show that Indonesian Stock Exchange Market does not show underperformance long-run IPO, and there is a positive relationship between the number of shares offered at the going public period and its long-term performance. However, the other variables used (i.e. age, time lag, and company size) do not influence the long-run IPO performance in Indonesian Stock Exchange. Keywords: initial public offering, long run performance, underperformance